A Study on Special Education for Exceptional Children’s: Exploring the Advancement and Impact of Special Education on Exceptional Children (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Education is simply a part of the overall education framework and progressive schools dedicated to an equal education for everybody are given. It is a versatile and independent child care scheme for special needs. This article presented a brief historical advancement of education for extraordinary children, preceded by the advancement, of Indian constitution, of many acts to educate and rehabilitate physically impaired children.Identifying the interests of individuals with special needs and organizing suitable educational environments to take into consideration their needs is the best way for them to become independent and active citizens in their communities. There are numerous educational environments such as special education classes, special schools and mainstream classrooms in which students with special needs fulfil their educational needs. In standard schools, also known as comprehensive schooling, the schooling of children with special needs is the most common activity in this respect.